Accompaniment of Initial Training Pedagogical Practices: A Self-Study Based on the Role as a Guide Teacher - Vanegas-Ortega, C (ORGANIZACION ESTADOS IBEROAMERICANOS EDUCACION CIENCIA & CULTURA-OEI, 2020)
In the context of my experience as a high school teacher of Biology and Sciences, 5 years ago, and while I was a teacher-in-training, accidentally I became the guide for other future Biology and Sciences teachers. This created some tension in my professional life because it blurred the lines between my role as a classroom teacher and my role as a guide for other teachers-in-training. In this situation, I decided the goal of my research would be to characterize the transformation of my own self-reflective processes through self-study of the role of a mentor and teacher of pedagogical practices in Biology and Sciences. The results show a tension in my identity process with this new role, allowing me to differentiate my role as a classroom teacher, and move forward towards a new identity as a teacher trainer or guide. In addition, it allowed me to understand my own educational practices from a more complex point of view, which allows for the inclusion of triad perspectives, the problematization of theory and classroom experiences, as well as realizing the high impact and influence which personal/family and emotional relations have in the ways one interacts with students and teachers-in-training.